Kingfisher voyages. Space - Goldsmith, Mike, Dr.; Ride, Sally (Boston : Kingfisher, 2005)
Presents full-color illustrated photographs and drawings that describes space exploration, and provides information on the layers of a spacecraft and space suit, the story of a space shuttle launch, short profiles of American and Soviet astronauts, and more.
Spiral-bound.
Includes index.
Booklist.
Library Media Connection.
7.0
3-6
Keywords: Astronautics -- Juvenile literature; Astronautics; Astronautics; Space flight; Astronautics; Outer space; Outer space -- Juvenile literature; Outer space; Outer space